Solving Controversies on the Iron Phase Diagram Under High Pressure. Issue 20 (25th October 2018) - Morard, Guillaume; Boccato, Silvia; Rosa, Angelika D.; Anzellini, Simone; Miozzi, Francesca; Henry, Laura; Garbarino, Gaston; Mezouar, Mohamed; Harmand, Marion; Guyot, François; Boulard, Eglantine; Kantor, Innokenty; et al.
Abstract: As the main constituent of planetary cores, pure iron phase diagram under high pressure and temperature is of fundamental importance in geophysics and planetary science. However, previously reported iron‐melting curves show large discrepancies (up to 1000 K at the Earth's core–mantle boundary, 136 GPa), resulting in persisting high uncertainties on the solid‐liquid phase boundary. Here we unambiguously show that the observed differences commonly attributed to the nature of the used melting diagnostic are due to a carbon contamination of the sample as well as pressure overestimation at high temperature. The high melting temperature of pure iron under core‐mantle boundary (4250 ± 250 K), here determined by X‐ray absorption experiments at the Fe K‐edge, indicates that volatile light elements such as sulfur, carbon, or hydrogen are required to lower the crystallization temperature of the Earth's liquid outer core in order to prevent extended melting of the surrounding silicate mantle. Plain Language Summary: Iron is the main constituent of planetary cores; however, there are still large controversies regarding its melting temperature and phase diagram under planetary interior conditions. The present study reconciles different experimental approaches using laser‐heated diamond anvil cell with different in situ X‐ray diagnostics (absorption, diffraction, and Mossbauer spectroscopy). The main reason of discrepancies (over 1000 K at core‐mantle boundary conditions) is attributed to carbon contamination from the diamond anvils and metrology issues related to thermal pressure overestimation. A high‐melting temperature for iron at core‐mantle boundary pressure would imply the presence of volatile elements in the liquid outer core, such as sulfur, carbon, or hydrogen, in order to lower its crystallization temperature and avoid extended melting of the surrounding silicate mantle. Key Points: Melting curve and phase diagram of pure Fe has been measured by in situ X‐ray absorption up to 130 GPa Overall agreement between different in situ studies leads to a melting temperature of 4250 ± 250 K at core‐mantle boundary pressure Discrepancies with previous measurements is unambiguously attributed to carbon contamination from the diamonds or thermal pressure overestimation